Development and identification of high yielding strain of Calocybe indica based on the multilocation trials - Sharma, V P; G, Heera; Kumar, Satish; Nath, Manoj (Mushroom Research, 2020)
Calocybe indica, a tropical mushroom commonly known as milky mushroom. Generation of the high yielding strains is one the major aim of the breeding progarmme. The three years milky mushroom cultivation trial in the various location during 2017-2020 resulted into the identification of the high yielding strain- DMR Milky-985. This strain has the spherical pileus and long stipe, while the pileus diameter and stipe length was 8 cm and 12 cm, respectively. Additionally, higher average fruit body weight was found in the DMR Milky-985 (47 g) then control-DMRO-334 (38 g). The higher biological efficiency (55.7%) was observed in DMR Milky-985 as compare with control (52.6%). Further, 5.6 per cent yield increase was observed in the DMR Milky-985 as compare with the control.